The Analogical Reasoning Thinking Process Viewed from Self-Efficacy - Fitrianto Eko Subekti; Y. L. Sukestiyarno; Wardono Wardono; Isnaini Isnaini (Universitas Negeri Semarang, 2021)
This study aims to describe the analogical reasoning thinking process in terms of self-efficacy on set material. Student self-efficacy data were obtained through questionnaires, while analogical reasoning deemed process data received from tests and in-depth interviews. The sampling method was using the purposive sampling technique. Data analysis used the stages of data reduction, data presentation, and concluding. The study results show that: Respondents with moderate self-efficacy tended not to understand the concept of a combination of sets, which resulted in an inability to solve problems related to intersection and combination questions in the three sets. Respondents with high self-efficacy tend to determine the pattern of the relationship between a slice and a combination of two sets with a piece and a variety of three sets. And 3) respondents with moderate and high self-efficacy tend to solve set problems using Venn sets' help.